ON RECENT -BIL DERIVATIVES IN ROMANIAN (Analele Universității București. Limba și literatură română, 2024)
The paper investigates a corpus of 72 recent -bil derivatives, used mainly in contemporary Romanian journalese (Croitor 2021). The paper shows that -bil adjectives in Romanian fall into two categories: fully eventive adjectives, characterized by thepresence of by-phrases and/or adverbial event modifiers and fully stative adjectives, simply indicating a property of the referent (Oltra-Massuet 2013). A second result of the analysis is the fact that the boundary between the two identified classes is blurry, in the sense that -bil adjectives actually form a continuum from eventive adjectives to fully stative -bil adjectives (Wasak 2021). Thirdly, the productivity of -bil can be explained by means of usefulness, fashion, and nameability (Plag 2002).